2022
DOI: 10.3389/fmicb.2022.945498
|View full text |Cite
|
Sign up to set email alerts
|

Pyoluteorin and 2,4-diacetylphloroglucinol are major contributors to Pseudomonas protegens Pf-5 biocontrol against Botrytis cinerea in cannabis

Abstract: Pseudomonas protegens Pf-5 is an effective biocontrol agent that protects many crops against pathogens, including the fungal pathogen Botrytis cinerea causing gray mold disease in Cannabis sativa crops. Previous studies have demonstrated the important role of antibiotics pyoluteorin (PLT) and 2,4-diacetylphloroglucinol (DAPG) in Pf-5-mediated biocontrol. To assess the potential involvement of PLT and DAPG in the biocontrol exerted by Pf-5 against B. cinerea in the phyllosphere of C. sativa, two knockout Pf-5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…protegens Cab57, was not pathogenic on plants, such as B. caryophylli strains. We expect that the usefulness of P. protegens Cab57 and its transformants can be further demonstrated by introducing other modifying enzymes for bacterial polyynes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…protegens Cab57, was not pathogenic on plants, such as B. caryophylli strains. We expect that the usefulness of P. protegens Cab57 and its transformants can be further demonstrated by introducing other modifying enzymes for bacterial polyynes.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas protegens strains are well-known as biocontrol agents that protect crops from pathogens (e.g., fungi, oomycetes, and nematodes). We recently identified new bacterial polyynes, protegenins A–D, from P. protegens Cab57 by genome mining (Figure A) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that pyoluteorin and 2,4-DAPG play a crucial role in the P. protegens Pf-5 biocontrol against B. cinerea . Moreover, pyrrolnitrin is known for its broad-spectrum antimicrobial activity and low phototoxicity which has made it an interesting target for biotechnological investigations ( Pawar et al., 2019 ; Balthazar et al., 2022b ). Cluster Blast analysis showed that all five of the highly similar BGCs are conserved within the Pseudomonas genus, and most of them are specific to the P. protegens species.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic concentrations on plant surfaces or in the soil, however, are considerable if not exponentially lower than those obtained in culture media [144]. Despite this difference, the role of antibiotics produced by biocontrol agents in the suppression of many plant diseases in planta has been confirmed through the use of mutant strains that are unable to produce antibiotics and do not suppress disease symptoms [109].…”
Section: Non-volatile Antimicrobial Compounds Antibioticsmentioning
confidence: 99%